Calappa Weber 1795 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Calappa Weber, 1795 Type species. Cancer granulatus Linnaeus, 1758 [Type locality: erroneously given as “America”]. Remarks. Linnaeus (1758: 627) stated that his Cancer granulatus inhabits America, however this species is actually known from the eastern Atlantic (Gulf of Biscay to Cape Verde) and Mediterranean Sea. The genus is worldwide in distribution, mainly in tropical and subtropical zones. Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 23, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155